To solve the equation x^2 + 2x – 3 = 0, we can use the quadratic formula:

x = (-b ± √(b^2 – 4ac)) / (2a)

In this equation, a, b, and c represent the coefficients of the quadratic equation:

a = 1 (coefficient of x^2) b = 2 (coefficient of x) c = -3 (constant term)

Now, let’s plug these values into the quadratic formula:

x = (-2 ± √(2^2 – 4(1)(-3))) / (2(1))

First, calculate what’s inside the square root:

2^2 – 4(1)(-3) = 4 + 12 = 16

Now, we can continue:

x = (-2 ± √16) / 2

Take the square root of 16:

x = (-2 ± 4) / 2

Now, we have two possible solutions:

- x = (-2 + 4) / 2
- x = (-2 – 4) / 2

Let’s calculate each solution separately:

- x = (2) / 2 = 1
- x = (-6) / 2 = -3

So, the solutions to the equation x^2 + 2x – 3 = 0 are:

x = 1 and x = -3